TAZKIYATUN NAFS CURRICULUM DEVELOPMENT IN JUNIOR HIGH SCHOOL (Analysis of Concepts Tazkiyatun Nafs by Ahmad Anas Karzon and its Implementation in Junior High School) - Hisan Mursalin (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2018)
Islam considers that education is not only as a process of transfer and transformation of knowledge naturally, but also a mandate that aims to make students to be a person who has divine personality (robbani), good moral and makes his life be more qualified due to the increase of spirit of faith in his soul; worthwhile both in the world and in the hereafter for him. Purification of soul or Tazkiyatun nafs is very important in the life of a human being. The soul determines whether an action is good or bad because a clean soul will produce taintless behavior while a bad soul will produce bad behavior and morals.This is certainly related to the tazkiyatun nafs concepts which have been explained by the scholars in which the concept of purification of soul is a spiritual need in the form of the teaching of din (Islam), tarbiyah, and tazkiyah for the soul. The human orientation today that prioritizes material does not guarantee the happiness of life. Facts have spoken that life's confusion and mental drought have mushroomed everywhere.The purpose of applying the concept of tazkiyatun nafs to the education is to lead the formation of a noble Muslim figure, with the same educational goals; human perfection in terms of taqarrub (to closer) to Allah, and happiness in the world and the hereafter. While the difference is when education is oftentimes merely taught without any guidance and direction in carrying out the morality or worship taught. Therefore, current education should do the soul purification at first so as the worship performed imprints on human heart and behavior.The focus of the problem in this study is to develop the Tazkiyatun Nafs curriculum appropriate with the age of junior high school students. Development of the curriculum is focused on developing goals, materials, methods, learning techniques, evaluation techniques, patterns of interaction and its implementation in everyday life. In conducting this research, the writer applied field study type since the data needed to compile scientific work was obtained from the research field. The research used a qualitative approach aimed at understanding social phenomena from the view of or perspective of participants. The Participants were those who were invited to interview, observed, asked to provide data, opinions, thoughts and perceptions. In terms of the presentation of material was descriptive analysis because this study attempted to sharpen the analysis of the full description related to the concept of tazkiyatun nafs which was then implemented to junior high school students.The result of the observation about the implementation of the tazkiyatun nafs curriculum at Darussofa IT Junior High School showed that the implementation of curriculum in everyday life needs to be taken into account by fostering the inner piece experienced by students so that a sense of being watched by Allāh ﷺ will be grown.